Functionalization of boron-doped diamond with a push–pull chromophore via Sonogashira and CuAAC chemistry. Issue 58 (26th September 2018) - Raymakers, Jorne; Krysova, Hana; Artemenko, Anna; Čermák, Jan; Nicley, Shannon S.; Verstappen, Pieter; Gielen, Sam; Kromka, Alexander; Haenen, Ken; Kavan, Ladislav; Maes, Wouter; Rezek, Bohuslav
Abstract : Functionalization of boron-doped diamond with a push–pull chromophore via Sonogashira cross-coupling affords better photovoltaic performances as compared to functionalization via CuAAC. Abstract : Improving the performance of p-type photoelectrodes represents a key challenge toward significant advancement in the field of tandem dye-sensitized solar cells. Herein, we demonstrate the application of boron-doped nanocrystalline diamond (B:NCD) thin films, covalently functionalized with a dithienopyrrole–benzothiadiazole push–pull chromophore, as alternative photocathodes. First, a primary functional handle is introduced on H-terminated diamond via electrochemical diazonium grafting. Afterwards, Sonogashira cross-coupling and Cu(i ) catalyzed azide–alkyne cycloaddition (CuAAC) reactions are employed to attach the chromophore, enabling the comparison of the degree of surface functionalization and the importance of the employed linker at the diamond-dye interface. X-ray photoelectron spectroscopy shows that surface functionalization via CuAAC results in a slightly higher chromophore coverage compared to the Sonogashira cross-coupling. However, photocurrents and photovoltages, obtained by photoelectrochemical and Kelvin probe measurements, are approximately three times larger on photocathodes functionalized via Sonogashira cross-coupling. Surface functionalization via Sonogashira cross-coupling is thus considered the preferential method for the development of diamond-based hybrid photovoltaics.